A Long Shadow of World War II: Development of the National Security Concept in the United States - V. A. Veselov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In recent years, the history of World War II has transformed into a battleﬁeld in its own right in the ‘war of memory’. Besides the clear fact that the current attempts to revise the results of this war reﬂect the contemporary international tensions, yet another factor should be noted. The ‘shadow’ of the Second World War appears to be very long. It manifests itself not only in the contemporary system of international relations, but also in the fact that we still view the world around through the prism of concepts that appeared during the state of war and still bear its mark. Particularly, the concept of national security. This paper examines the emergence and development of this concept in the United States. The author notes that although the concept of national security existed throughout the 20th century, before World War II it was identiﬁed primarily with the defense of the state. The paper examines how lessons of the Second World War led to a rethinking of this concept, and how approaches to national security evolved during the war and immediately after it. Special attention is given to discussions that preceded the adoption of the National Security Act of 1947, as well as to its initial results. The author demonstrates that the national security concept was based on a fundamental recognition of the existence of a special state between peace and war. For successful functioning within this state, the government needs to rely on a wide range of tools of both economic and military-political and ideological nature. Based on the lessons from the war, national security was viewed as an ‘overarching structure’, aimed not only at integrating various components of the state’s policy, but also at eliminating any contradictions that may arise between them. On the other hand, the author emphasizes that from the very beginning the national security concept had a pronounced proactive, oﬀensive and expansionist character. Being considered as an antipode to the concept of collective security, this concept reﬂected the will of the US elites not only to get integrated in the existing system of international relations, but to create a new one, which would be based on the American values and would ensure the stable functioning of the US economy. The author concludes that it is precisely the multidimensionality of the national security concept caused by the multidimensional nature of the challenges of World War II that explains its continued relevance for the study of world politics.